Strategi Stimulasi Kecerdasan Linguistik Anak Usia Dini melalui Kegiatan Bermain di TK Insan Madani - Raihan Nazrey Suseno; Fauziah Nasution; Arneta Widia; Adam Malik; Anugrah Satria Dermawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aimed to analyze strategies for stimulating linguistic intelligence in early childhood through play-based activities at TK IT Insan Madani, Deli Serdang. The research employed a descriptive qualitative approach, with data collected through observation and interviews with kindergarten teachers. The results showed that play activities such as storytelling, role-playing, and the use of educational visual media consistently improved children's language abilities, including vocabulary enrichment, sentence structuring, and confidence in communication. Observations also revealed increased verbal interaction among children during classroom activities. These findings indicate that play-based learning is an effective strategy for developing linguistic intelligence in early childhood, especially when supported by a conducive learning environment and active involvement of teachers and parents.